Przygotowania studentów wychowania fizycznego do prowadzenia zajęć z zakresu edukacji zdrowotnej – teoria a rzeczywistość = The preparation of physical education students for health education lessons – theory and reality - Klimas, Nela; Laudańska-Krzemińska, Ida (Journal of Education, Health and Sport, 2015)
Klimas Nela, Laudańska-Krzemińska Ida. Przygotowania studentów wychowania fizycznego do prowadzenia zajęć z zakresu edukacji zdrowotnej – teoria a rzeczywistość = The preparation of physical education students for health education lessons – theory and reality. Journal of Education, Health and Sport. 2015;5(11):650-660. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35714 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A650-660 http://pbn.nauka.gov.pl/works/684958 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Klimas Nela, Laudańska-Krzemińska Ida. Przygotowania studentów wychowania fizycznego do prowadzenia zajęć z zakresu edukacji zdrowotnej – teoria a rzeczywistość. Quality in Sport. 2015;1(2):43-52. eISSN 2450-3118. The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. Nela Klimas, Ida Laudańska-Krzemińska Zakład Nauk o Aktywności Fizycznej i Promocji Zdrowia Akademia Wychowania Fizycznego im. Eugeniusza Piaseckiego w Poznaniu Przygotowania studentów wychowania fizycznego do prowadzenia zajęć z zakresu edukacji zdrowotnej – teoria a rzeczywistość The preparation of physical education students for health education lessons – theory and reality Streszczenie Celem artykułu była konfrontacja wymagań nowej podstawy programowej w związku z wyeksponowaniem w niej roli edukacji zdrowotnej i powiązania jej z wychowaniem fizycznym z rzeczywistym przygotowaniem studentów do realizacji zadań tej edukacji. Badania przeprowadzono w roku akademickim 2014/2015 w Akademii Wychowania Fizycznego w Poznaniu wśród 51 studentów pierwszego roku SUM kierunku Wychowanie Fizyczne. Wykorzystano metodę sondażu diagnostycznego z anonimowym kwestionariuszem ankiety. Z badań własnych wynika, że szczególnie duże wyzwanie stanowią treści związane ze zdrowiem psychospołecznym oraz kształtowaniem umiejętności życiowych u dzieci i młodzieży. Słowa kluczowe: edukacja zdrowotna, podstawa programowa kształcenia ogólnego, kształcenie nauczycieli. Abstract The aim of the study was to confront the requirements of the new core curriculum, changing the status of school-based health education and linking it strongly with physical education (PE), with the actual preparation of students to conduct health education lessons. The survey was conducted in the academic year 2014/2015 at the Eugeniusz Piasecki University of Physical Education in Poznan, among 51 physical education master’s students. The diagnostic survey method based on the authorial and anonymous questionnaire was used. According to the study results one of the most challenging tasks of future PE teacher are those connected with psychosocial health and developing life skills among children and youth. Key words: health eduaction, core curriculum, teacher education.